QCA and CMOS Nanotechnology Based Design and Development of Nanoelectronic Security Devices with Encryption Schemes - Devendra K. Verma; P. K. Barhai; V. Nath (Institute of Advanced Engineering and Science, 2015)
In WiMAX/WiFi Wireless Environment the Transfer of Data/Information is vulnerable to external attacks as it takes place through an open-air medium. The Data/Information is vulnerable to Jamming, Detection, Interception, Network Injection, Interruption, Modification, Packet Scrambling, Fabrication, Unauthorised forwarding and Denial-of-Service (DoS). Our Research Work focuses on ‘QCA & CMOS Nanotechnology based Design & Development of Nanoelectronic Security Devices with Encryption Schemes to provide/enhance Security and Privacy for WiMAX/WiFi/Satellite Wireless Communication Systems. The Schemes are based on Dynamic Channel Hopping, Random Channel Selection, Cryptography and Encryption of Information/Data/Control Codes. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7485